Individual and organizational psychosocial predictors of hospital doctors’ work-related wellbeing: a multilevel and moderation perspective - Teoh, Kevin R.H.; Hassard, Juliet; Cox, Tom (Lippincott Williams & Wilkins, 2020)
Background: The high prevalence of burnout and depression among doctors highlights the need to understand the psychosocial antecedents to their work-related wellbeing. However, much of the existing research has been a-theoretical, operationalized a narrow measurement of wellbeing, and predominantly examined such relationships at the individual level. Purpose: This study uses a multilevel perspective to examine individual (i.e., job demands and resources) and organizational level psychosocial predictors of three measures of work-related wellbeing: perceived stress, presenteeism and work engagement. The Job Demands-Resources (JD-R) theory underpins the postulated relationships. Methodology: The 2014 National Health Service Staff Survey was analyzed using multilevel modelling in MPlus. The dataset involved 14,066 hospital-based doctors grouped into 157 English hospital organizations (i.e., Trusts). Results: Congruent with the JD-R, job demands (workplace aggression and insufficient work resources) were stronger predictors of perceived stress and presenteeism than job resources. Equally, job resources (job control and manager support) were generally stronger predictors of work engagement than job demands. At the organizational level-bed occupancy rates and number of emergency admissions predicted work engagement. No hypothesized individual or multilevel interactions were observed between any of the job demands and resources. Practical Implications: The findings emphasize that a broader perspective of work-related wellbeing among hospital doctors should be employed, and the empirical value of examining such relationships from a multilevel perspective. Successful health intervention should target the appropriate antecedent pathway, and recognize the role of organizational level factors when trying to manage hospital doctors’ work-related wellbeing.